Product Sorting System In Checker Sorting Process Using The Template Matching Method - Joko Priambodo; Fauzi Imaduddin Adhim; Enny Indasyah (Universitas Nahdlatul Ulama Surabaya, 2022)
In supporting the production activities of a company, an infrastructure unit is needed that is capable of supporting the production activities of a company. Several companies that produce animal feed and processed food have problems related to the failure of the sorting process. The sorting process for checking packaged products is still carried out by human power, so errors often occur due to human negligence in sorting packaged products. Therefore a tool is designed to sort automatically and be able to distinguish differences from packaged products using image processing with the Template Matching method. Then, proceed with looking for accurate calculations using the Template Matching algorithm, which will help detect differences between packaging products A and B. The technique used in the method is the calculation of values using greyscale imagery and image segmentation with ten trials based on the labels on the template features used. After testing, the best accuracy results, namely 59% obtained on image segmentation